2017
DOI: 10.1155/2017/5089752
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation between IP-10 and IFN-γLevels in Rhesus Monkeys(Macaca mulatta)with Either Naturally Acquired or Experimental Infection ofMycobacterium tuberculosis

Abstract: Numerous studies identify that IP-10 and IFN-γ are involved in leucocyte migration and activation and regarded as promising surrogate biomarkers in human and bovine tuberculosis infection, but there is lack of evidence for IP-10 in nonhuman primates. In this study, we directly determined IP-10 and IFN-γ levels in plasma from 30 healthy monkeys, 30 monkeys with naturally acquired tuberculosis, 4 monkeys experimentally infected with tuberculosis, and PPD stimulated whole blood of 14 monkeys with naturally acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
5
6
1
Order By: Relevance
“…In the current study, the results revealed highly significant elevation in serum IFN-γ level (Table 1) in newly diagnostic TB patients, relapse TB patients and healthy controls (P<0.001and P<0.014, respectively). These results are consistent with previous studies showing elevated plasma levels of IFN-in newly diagnosed TB patients and relapse TB patients suggesting up-regulation in the proinflammatory response (18,19).…”
Section: Discussion: Serum Ifn-γ Levelsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, the results revealed highly significant elevation in serum IFN-γ level (Table 1) in newly diagnostic TB patients, relapse TB patients and healthy controls (P<0.001and P<0.014, respectively). These results are consistent with previous studies showing elevated plasma levels of IFN-in newly diagnosed TB patients and relapse TB patients suggesting up-regulation in the proinflammatory response (18,19).…”
Section: Discussion: Serum Ifn-γ Levelsupporting
confidence: 93%
“…The fact that serum IFN-γ levels are up-regulated in the newly diagnosed TB patients indicates innate protective response during early phase of M. tuberculosis infection. The results of the current study agree with previous studies (19)(20)(21)(22)(23).These findings could be referred to possibility of developing immune-prognostic assays based on new biomarkers detection.…”
Section: Discussion: Serum Ifn-γ Levelsupporting
confidence: 92%
See 1 more Smart Citation
“…14,[17][18][19] This study aimed to evaluate more cytokines as alternative biomarkers of whole-blood stimulation assays in diagnosing nonhuman Panel 1 6 TNF RII, IL19, RANTES, MIF, MPO, Galectin-3 Panel 2 37 IFN-γ, TNF-α, TNF RI, GM-CSF, IL1β, IL1RA, IL1 RII, IL2, IL2 Rα, IL4, IL5, IL6, IL6 Rα, IL8, IL10, IL15, IL17A, IL22, MCP-1, MIP-1β, MCP-3, MCP-4, CCL11, CCL18, CCL22, CCL27, CXCL1, CXCL4, IP-10, CXCL12, CXCL13, CD14, CD27, CD30 been proven to be robust biomarkers of whole-blood stimulation assays. [22][23][24] In our study, IFN-γ and IP-10 were also identified as sensitive markers for the PPD-based whole-blood stimulation assay in nonhuman primates, and IP-10 appeared to be more sensitive than…”
Section: Discussionsupporting
confidence: 50%
“…With live bacterial vaccine/infection, functional antagonistic co-regulation of the observed response by Th17 and Treg cells is likely to occur-an area for future investigation. Both DVC and USAMRIID-LVS also induced production of the cytokines IFN-γ and IP-10, which are known to be regulators of activated T lymphocytes and have been suggested as potential biomarkers for other bacterial infections such as M. tuberculosis [43].…”
Section: Discussionmentioning
confidence: 99%